Height outcome of the recombinant human growth hormone treatment in patients with SHOX gene haploinsufficiency: a meta-analysis. (April 2013) - Massart, Francesco; Bizzi, Martina; Baggiani, Angelo; Miccoli, Mario
Background: Patients with mutations or deletions of the SHOX gene present variable growth impairment, with or without mesomelic skeletal dysplasia. If untreated, short patients with SHOX haplodeficiency (SHOXD) remain short into adulthood. Although recombinant human growth hormone (rhGH) treatment improves short-term linear growth, there are episodic data on the final height of treated SHOXD subjects.Patients & methods: After a thorough search of the published literature for pertinent studies, we undertook a meta-analysis evaluation of the efficacy and safety of rhGH treatment in SHOXD patients.Results: In SHOXD patients, administration of rhGH progressively improved the height deficit from baseline to 24 months, although the major catch-up growth was detected after 12 months. The rhGH-induced growth appeared constant until final height.Conclusion: Our meta-analysis suggested rhGH therapy improves height outcome of SHOXD patients, though future studies using carefully titrated rhGH protocols are needed. Original submitted 29 October 2012; Revision submitted 22 February 2013